Inositol-6 phosphate inhibits the mTOR pathway and induces autophagy-mediated death in HT-29 colon cancer cells - Pandurangan, Ashok Kumar; Ismail, Salmiah; Mohd Esa, Norhaizan; Munusamy, Murugan A. (Termedia Publishing, 2018)
Introduction: Colorectal cancer (CRC) is common, with a worldwide incidence estimated at more than 1 million cases annually. Therefore, the search for agents for CRC treatment is highly warranted. Inositol-6 phosphate (IP6) is enriched in rice bran and possesses many beneficial effects. In the present study the effect of IP6 on autophagy-mediated death by modulating the mTOR pathway in HT-29 colon cancer cells was studied. Material and methods: Autophagy was assessed by acridine orange (AO) staining, transmission electron microscopy, and western blotting to detect LC3-II and Beclin 1. Akt/mTOR signaling protein expression was also analyzed by western blotting. Apoptosis was analyzed by annexin V staining. Results: Incubation of cells with IP6 resulted in downregulation of the p-Akt at 3h. Along with that confocal microscopic analysis of p-AKT, IP6 administration resulted that a diminished expression of p-Akt. mTOR pathway regulates autophagy and incubation with IP6 to HT-29 cells showed decreased expression of p-70S6Kinase, 4-EBP-1 in a time-dependent manner. Inositol-6 phosphate (10 μg/ml, 24 and 48 h) induced autophagic vesicles, as confirmed by AO staining and transmission electron microscopy. We also found increased expression of LC3-II and Beclin 1 in a time-dependent manner after incubation with IP6. Furthermore, IP6 induced apoptosis, as revealed by annexin V staining. Conclusions: Our results clearly indicate that IP6 induces autophagy by inhibiting the Akt/mTOR pathway.